Pengaruh manajemen perubahan terhadap kepuasan pengguna jasa kelompok mahasiswa dan dampaknya terhadap peningkatan kualitas kerja pegawai pada Terminal Kertojoyo Mojokerto - Nuraeni, Eny (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Terminal as road transport infrastructure in carrying out its function as a place of need to raise and lower people or goods, resting place for bus and vehicle crew before starting the trip again, and arranging arrival and departure of public transportation, which is the shape of transportation network node. The purpose of this research are: 1) To know and analyze the effect of routine change to the improvement of work quality of employees. 2) To know and analyze the effect of improvement changes to the improvement of work quality of employees. 3) To know and analyze the effect of innovative change on the improvement of work quality of employees. 4) To know and analyze the effect of routine changes on student service group student satisfaction. 5) To know and analyze the effect of improvement changes on student service group user satisfaction. 6) To know and analyze the effect of innovative change on student service group satisfaction. 7) To know and analyze the effect of improving the quality of work of employees to the satisfaction of student service group. 8) To know and analyze the influence indirectly Management of changes to user satisfaction services group of students through the variable between improving the quality of work employees. This research was conducted at Terminal Kertojoyo Mojokerto, while the time of the research was conducted in August 2016. The population in this research is the user of student group service of Kertojoyo Mojokerto Terminal, from the very large population and the unknown number, using Cochran formula taken samples of 73 respondents . From the results of the study can be concluded as follows: 1) Regular changes have no significant effect on the quality improvement of employee. 2) Changes in the increase significantly affect the improvement of employee quality. 3) Innovative changes have a significant effect on improving the quality of work of employees. 4) Regular changes have a significant effect on student service group user satisfaction. 5) Changes in the increase significantly affect the user satisfaction of student group services. 6) Innovative change has no significant effect on student service group user satisfaction. 7) Improving the quality of employees' work has no significant effect on student service group satisfaction. 8) Management of each change directly affects the user satisfaction of student services group through the variable between improving the quality of work of employees.